Penormaan dan Pelaksanaan Kewajiban Ingkar Notaris - Qonitah Annur Aziza; Aprilia Trisanti; Kiki Aristyanti (Faculty of Law Hang Tuah University, 2020)
The notary is obliged to keep all legal deeds outlined in the contents of the deed and all information given to the notary in making the deed. the appointment of a notary as a witness in a case causes the violation of this obligation to be violated a lot. Strong legal protection is needed from the Honorary Board of Notaries (MKN) so that investigators and prosecutors are not arbitrary. The formulation of the problem taken by the author is the normalization of notary liability based on UUJN. And the application of sanctions from the notary obligation in the community.The writing of this thesis uses a normative juridical research method, namely by reviewing the legal norms contained in legislation, legal theories and jurisprudence related to the issues discussed. This research approach uses a statute approach and a conceptual approach. The purpose of this study is to explain more deeply about the norms of denial obligations in the UUJN and their application in the community with the existence of permission from MKN. Based on the results of the study, the author obtained answers to existing problems, namely the notary has a broken obligation that must be obeyed and regulated in Article 4 paragraph (2) and Article 16 paragraph (1) letter f UUJN-P. This breach obligation has a limit set out in UUJN in Article 66 paragraph (1) concerning a notary appointed as a witness can talk about the deed with the approval of the permit from MKN. But it also needs to be known if the broken obligation is violated without permission, the notary may be subject to administrative sanctions in the form of termination of employment, civil sanctions in the form of compensation and criminal sanctions in the form of prison sentences.